PERAN AKUNTABILITAS DAN TRANSPARANSI TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DESA - Riska Febrianto; Mujiyati Mujiyati (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to understand the role of accountability and transparency in village financial management. The case study method was used in this research through interviews with village government officials. The results show that accountability and transparency are carried out by the village government vertically to the district/city government and horizontally to the community. This practice is considered to have complied with the Minister of Home Affairs Regulation No. 20 of 2018. However, the village government must fix the planning system and increase the participation of the Village Representative Body (BPD). These obstacles can be overcome by increasing the intensity of the aspiration of village representatives